Focusing on internal stakeholders to enable the implementation of organizational change towards corporate entrepreneurship : A case study from France - Chebbi, Hela; Yahiaoui, Dorra; Sellami, Mohamed; Papasolomou-Doukakis, Ioanna; Melanthiou, Yioula (My University, 2020)
Although previous studies have highlighted the importance of implementing corporate entrepreneurship to foster innovation within organizations, little emphasis has been placed on examining the concept from a change management perspective. In an attempt to bridge this gap, the current study aims at understanding the mechanisms and tools that top managers can use in order to involve internal stakeholders in driving a change process to adopt a corporate entrepreneurship strategy. The paper discusses the findings that emerged from an exploratory study carried out within “Poult”, a French biscuit manufacturer, which has embarked on an organization-wide effort to instil a culture of corporate entrepreneurship. The findings are examined in the context of stakeholder theory and Kotter's (1996) change model with a focus on the importance of internal marketing strategy during the change process. The contribution of managerial and organizational mechanisms towards fostering corporate entrepreneurship are highlighted.
Keywords: Internal marketing; France; Corporate entrepreneurship; Change process; Innovation; Internal stakeholders